Manajemen Fisioterapi pada Post Sectio Caesarea - Puji Eva Annisaa; Adnan Faris Naufal; Vivin Sari Sukmawati (Jurnal Anestesi, 2025)
Sectio Caesarea (CS) is a method of childbirth through surgery with an incision in the abdomen and uterus. The causative factors include narrow pelvis, placenta previa, fetal malpresentation, and fetal distress. According to WHO, the global caesarean delivery rate ranges from 5-15% per 1000 births. Physiotherapy plays an important role in improving functional ability after CS through movement, reducing pain, increasing muscle strength, and accelerating recovery. A 30-year-old female patient, G3P2A0, 39+5 weeks of gestation, came to Simo Boyolali Hospital with complaints of tight stomach and premature rupture of membranes. The CS operation was performed at 16.00 WIB. Postoperatively, the patient experienced abdominal pain that worsened when moving and had difficulty sitting and breast milk had not come out. The patient was given breathing exercises, pelvic floor exercises, and mobilization exercises every 2 hours with 8 repetitions. The results showed a decrease in pain and an increase in functional ability. The post-CS physiotherapy program with breathing exercises, pelvic floor exercises, and mobilization exercises was effective in reducing pain and increasing the patient's functional ability.